Adoption of International Financial Reporting Standards (IFRS) and Measurement of Reporting Quality: A Review of Methodologies - Abdullahi, Aminu; Abubakar, Musa Yelwa (International Business and Accounting Research Journal, 2017)
This paper conceptually review the various models employed by previous studies in the measurement of reporting quality following the adoption of International Financial Reporting Standards (IFRS) around the world. In the review, attention is paid to the nature, appropriateness and limitations of each of the models identified. It was found that, the methodologies used in studying the relationship and impact of IFRS on reporting quality are classified into qualitative, quantitative and firm-specific attributes models on one hand, and direct and indirect models on the other hand. Finally, the study calls on researchers to be wary, by selecting appropriate method that commensurates with the objectives of their studies, and their ability to adequately mitigate the limitation of the model highlighted in the review.